EKI TILLI SÓZLIK DÚZIWDE ZAMANAǴÓY LEKSIKOGRAFIYALÍQ QATNASLAR - Usaxov, Rustem Muratovich (SCIENCE and SOCIETY, 2026)
The article analyzes lexicographic relations in the creation of a modern bilingual dictionary. The study considers the integration of functional-systemic, typological-cognitive and translation-communicative components, as well as strategies for connecting national materials on the Karakalpak language.